THE CONCEPT OF MASS MEDIA DISCOURSE AND ITS FUNCTIONS - Ergasheva Arofat Tolib qizi (Лучшие интеллектуальные исследования, 2024)
Annotation: The subject of research in this article is the concept of mass media discourse. The purpose of the work is to research the mass media discourse in the context of modern society and practice of media communications. The work uses a set of methods: descriptive, comparative and interpretative methods.